Family functionality, friend support and academic performance in Odontology college students - Tamayo-Cabeza, Guillermo; Hernández-Alvarez, Arleth; Diaz-Cardenas, Shyrley (Universidad y Salud, 2021)
Introduction: Academic dropout in college students could be associated with family functionality, which could also negatively impact their academic performance. Objective: To describe the relationship between sociodemographic and family characteristics with family functionality, friend support, and academic performance in Odontology students from a public university in the city of Cartagena (Colombia). Materials and methods: A cross-sectional study was conducted with 438 students. A survey-type instrument was used to obtain information regarding sociodemographic variables as well as family and home characteristics. Data were analyzed using descriptive statistics and bivariate analysis with a Pearson’s Chi square test. Results: A statistically significant relationship was observed between students’ age and family functionality (p=0.0029). Likewise, a significant relationship was found between the origin of the students and friend support (p=0.0230), as well as between low education level and family functionality (p=0.0018). Conclusions: The identification of factors related to family functionality and friend support can contribute to determining important aspects to be considered for the design and implementation of academic interventions focused on Odontology students.